2017
DOI: 10.1038/s41598-017-14704-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effect of a traditional Chinese dietary habit—blending lard with vegetable oil while cooking

Abstract: Obesity, which is associated with dietary habits, has become a global social problem and causes many metabolic diseases. In China, both percentages of adult obesity and overweight are far lower compared to western countries. It was designed to increase the two levels of daily intake in human, namely 3.8% and 6.5%, which are recommendatory intake (25 g/d) and Chinese citizens’ practical intake (41.4 g/d), respectively. The mice were respectively fed with feeds added with soybean oil, lard or the oil blended by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 51 publications
2
22
1
Order By: Relevance
“…However, our results in this study conflict our previous research findings [22]. This may be due to differences in fat energy, as our previous study supplied 25% fat energy compared to 35% fat energy that was supplied in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, our results in this study conflict our previous research findings [22]. This may be due to differences in fat energy, as our previous study supplied 25% fat energy compared to 35% fat energy that was supplied in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…High fat diet with soybean oil induced high body weight more than high fat diet with palm oil and lard, which are both rich in SFAs [21]. In our previous study, traditional Chinese dietary habits of blending lard with SBO were proven to have anti-obesity effects when stimulated average oil intake of urban and rural residents in China [22]. This study aimed to investigate the effects of different fat/oil mixtures on lipid metabolism in mice when stimulated with typical Chinese residents' high fat diet.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our previous study (under 25% fat energy) found that a mixture of lard and soybean oil could reduce body fat accumulation compared to lard or soybean oil 20 , it was also proved in present study (under 30% fat energy), and can be extended to sun ower oil. However, under 35% fat energy, the function cannot be observed 21 .…”
Section: Discussionsupporting
confidence: 84%
“…However, in recent years, numerous randomized, double-blind controlled trials, and meta-analysis studies have found that compared with unsaturated fatty acids, intake of SFAs shows no significant difference in cardiovascular disease and obesity risks [23,24]. Previously, we established that a lard and soybean oil mixture was found to be beneficial for lipids metabolism in medium-fat diets [25]. In the present study, we explored the effectiveness of a lard and soybean oil mixture (an LFHC diet) in alleviating NAFLD.…”
Section: Introductionmentioning
confidence: 99%